School-based educational intervention to improve children’s oral health-related behaviors in rural Bangladesh (South East Asia Journal of Public Health, 2018)
Children in rural Bangladesh have limited access to oral health services. As a pilot project, a one-day one-time oral health educational intervention was conducted at a primary school in Tangail district in Bangladesh. This study assessed the effect of this educational intervention on the children’s oral behaviors using controlled pre- and post-intervention design. Fifty-two students at the intervention school and 37 students at a control school agreed to participate in this study. A baseline survey was conducted for children at both schools using a standardized semi-structured questionnaire. Children at the intervention school received face-to-face dental exercises and a group seminar. Six months after the intervention, a follow-up survey was conducted at both schools to compare changes in children’s oral behaviors at the two schools. The increase in the percentage of intervention-school participants who reported brushing their teeth two or more times per day between the baseline and follow-up surveys was 7.6 times greater than that in the control group (95% CI= 1.7–35.1; p